Reporting outcomes of definitive radiation-based treatment for esophageal cancer: a review of the literature. Issue 2 (1st March 2015) - Main, B. G.; Strong, S.; McNair, A. G.; Falk, S. J.; Crosby, T.; Blazeby, J. M.
Summary: Accurate evaluation of radical radiotherapy requires well designed research with valid and appropriate outcomes. This study reviewed standards of outcome reporting and study design in randomized controlled trials (RCTs) of radiation-based therapy for esophageal cancer and made recommendations for future work. Randomized controlled trials reporting outcomes of definitive radiation-based treatment alone or in combination with chemotherapy were systematically identified and summarized. The types, frequency, and definitions of all clinical and patient-reported outcomes (PROs) reported in the methods and results sections of papers were examined. Studies providing a definition for at least one outcome and presenting all outcomes reported in the methods were classified as high quality. From 142 5 abstracts, 16 RCTs including 1803 patients were identified. The primary outcome was overall survival in 13 studies, but five different definitions were reported. Outcomes for treatment failure included local, regional, and distant failures, and inconsistent definitions were applied. An observer assessment of dysphagia was reported in seven RCTs but PROs were reported in only one. Only three RCTs were at low risk of bias, with all lacking reports of sequence generation and only a minority reporting allocation concealment. The quality of outcome reporting in RCTs was inconsistent and risked bias. A core outcome set including clinical and PROs is needed to improve reporting of trials of definitive radiation-based treatment for esophageal cancer.